TATA-binding protein and nuclear differentiation in Tetrahymena thermophila. - Stargell, L A (1994)
Unambiguous TATA boxes have not been identified in upstream sequences of Tetrahymena thermophila genes analyzed to date. To begin a characterization of the promoter requirements for RNA polymerase II, the gene encoding TATA-binding protein (TBP) was cloned from this species. The derived amino acid sequence for the conserved C-terminal domain of Tetrahymena TBP is one of the most divergent described and includes a unique 20-amino-acid C-terminal extension. Polyclonal antibodies generated against a fragment of Tetrahymena TBP recognize a 36-kDa protein in macronuclear preparations and also cross-react with yeast and human TBPs. Immunocytochemistry was used to examine the nuclear localization of TBP during growth, starvation, and conjugation (the sexual phase of the life cycle). The transcriptionally active macronuclei stained at all stages of the life cycle. The transcriptionally inert micronuclei did not stain during growth or starvation but surprisingly stained with anti-TBP throughout early stages of conjugation. Anti-TBP staining disappeared from developing micronuclei late in conjugation, corresponding to the onset of transcription in developing macronuclei. Since micronuclei do not enlarge or divide at this time, loss of TBP appears to be an active process. Thus, the transcriptional differences between macro- and micronuclei that arise during conjugation are associated with the loss of a major component of the basal transcription apparatus from developing micronuclei rather than its appearance in developing macronuclei.